Inclusion complexes of cyclodextrin with whey peptides: characteristic of antioxidant activity - Halavach, Tatsiana M.; Tarun, Ekaterina I.; Zhygankov, Vasiliy G.; Butina, Anastasia D.; Kurchenko, Vladimir P. (Experimental Biology and Biotechnology, 2019)
A comparative analysis of organoleptic and antioxidant properties of βcyclodextrin clathrates with peptides of whey proteins was carried out. According to the data of thermogravimetric analysis the formation of inclusion complexes was confirmed and the increase in thermal stability of peptides in composition of clathrates was established. The reduction in bitter taste of the experimental complexes by 20 –70 % and the increase in antiradical activity in 1.3–1.6 times compared to initial hydrolysate was shown. With the raise in complexation temperature from 25 to 50 °C the increase in antioxidant effect and the improvement in organoleptic properties of clathrates were achieved. Perspective is the use of milk protein hydrolysates with pronounced bitter taste in the composition of biologically active inclusion complexes with βcyclodextrin which have acceptable organoleptic properties and high antioxidant potential.